Erratum: Measurement of CP observables in B±→DK[star]± decays using two- and four-body D final states - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2018)
The measurements of Aππ and RKK in B±→DK*± decays were incorrectly reported in the paper [1], due to a transposition of the systematic uncertainties. This error was present in the reporting of the individual systematic uncertainties, the correlation matrix, and in the calculation of RCP+.
Im Titel sind "+" und "-" untereinander geschrieben: "+" hochgestellt, "-" tiefgestellt
Im Titel ist "star" hochgestellt
Im Titel wird "star" als griechischer Buchstabe dargestellt
The LHCb Collaboration: R. Aaij, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, M. Dziewieck, D. Gerick, J.P Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecná, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, A. Piucci, M. Stahl, S. Stemmle, J. van Tilburg, U. Uwer, A. Zhelezov [und weitere]
Gesehen am 11.07.2019